Law and legal theory - Brooks, Thom. (Studies in Moral Philosophy, 2014)
What is the relation between law and democracy and how might it be improved? What values should inform the body of laws that govern us all? How should we determine crimes from non-crimes? What justifies state punishment, if anything? Law and Legal Theory brings together some of the most important essays in the area of the philosophy of law written by leading, international scholars and offering significant contributions to how we understand law and legal theory to help shape future debates. Contributors include Christopher Bennett, Samantha Besson, Thom Brooks, Brian Butler, Sean Coyle, Rowan Cruft, Leonard Kahn, Richard Lippke, Andrew March, Matt Matravers, Adina Preda, Maria Cristina Redondo, Hanoch Sheinman and Leo Zaibert.